Penerapan Terapi Akupresur Terhadap Penurunan Tekanan Darah Pada Lansia Yang Mengalami Hipertensi - Putri, Selvia Purnama; Metasari, Des; Sari, Tsuraiya Indah Permata; Jayanti, Devitri; Putra, Dicky Candra; Saputra6, Dandi; r, Tuti; Azissah, Danur (Jurnal Gotong Royong, 2025)
Hypertension is one of the major health issues commonly experienced by the community, especially among the elderly. A lack of understanding regarding blood pressure management methods poses a significant challenge in controlling this condition. This community service program aims to raise awareness and improve residents' skills in managing hypertension through acupressure therapy as a non-pharmacological approach.The program was conducted in RT 03, Ponorogo Subdistrict, using methods such as education, demonstrations, and hands-on practice. Participants were provided with an understanding of the definition of hypertension, its causes, impacts, and the benefits of acupressure therapy in lowering blood pressure. Training sessions focused on practicing specific acupressure points on the body, accompanied by blood pressure measurements taken before and after the therapy sessions. The results indicated a reduction in participants' blood pressure levels following acupressure therapy. Additionally, participants' knowledge regarding hypertension and its management improved significantly. In conclusion, acupressure therapy has proven to be an effective and practical solution that can be independently applied to manage blood pressure and prevent hypertension-related complications in the community.